Students' Attitudes toward the Annual Instrumental Exam in Croatian Elementary Music Schools - Jasna Šulentić Begić; Amir Begić; Ivana Sabolek (Journal on Efficiency and Responsibility in Education and Science)
At the end of the school year, the music schools organize the annual instrumental exam to evaluate the student's achievements. The study investigates complex patterns of performance anxiety in music school students during annual exams, focusing on how gender, age, instrument type, and family musical tradition interact, revealing inconsistencies with prior research and illustrating the importance of tailored pedagogical interventions. The study was conducted on a sample of 143 third- to sixth-grade students, using a 14-item Likert-scale questionnaire. Results show high levels of pre-exam stress, especially among girls and piano students, while younger students reported more positive emotions before the exam and older students were calmer afterward. Family music tradition had limited influence. These findings underscore the need to rethink evaluation approaches in music education with an emphasis on students' emotional well-being. Teachers and parents must create a supportive and positive environment before and during the exam, particularly for girls. The study also has practical implications: it emphasizes that there must be psychological preparation for exams, emotional intelligence development, and consideration of alternative assessment methods that reduce stress.